The Moveable Goods as a Collateral Object in Warehouse Receipt System - Ninis Nugraheni (Fakultas Hukum Universitas Hang Tuah, 2018)
The Law of Warehouse Receipt (Act No. 9/2006 about Warehouse Receipt System) has defined a new collateral object called Warehouse Receipt. Warehouse Receipt is a proof of ownership of a commodity that can be negotiable, exchanged and pledged. This article used Normative Juridical Assessment by assessing and analyzing the primary, secondary and tertiary legal material. It is related to the Law of Banking, generally in collateral, and particularly in Act No. 9/2006 about Warehouse Receipt System. Warehouse Receipt as a negotiable instrument can be classified into moveable goods. Such classification is based on an argument that Warehouse Receipt has an economical value. Thus, it can be used as a collateral object. Warehouse receipt as a pledged moveable good may comply with the terms of execution in pledge.